Addressing unsolved educational problems about linguistically diverse children: perspectives of early childhood educators in South Korea. Issue 4 (21st April 2022) - Lew, Shim; Choi, Jayoung
ABSTRACT: Despite efforts to adopt inclusive education practices and foster cultural competence in classrooms across the globe, adequate training and shifts in teachers' mindsets frequently seem to lag behind. Studies continue to find that teachers in a variety of contexts hold negative views of culturally and linguistically diverse (CLD) families. Individual teachers' attitudes and perspectives may take on more primacy in schools where CLD populations are relatively low and thus targeted interventions and policies to support multicultural and multilingual learners are not in place. This study applied culturally and linguistically responsive teaching frameworks to explore perceptions about CLD students among mainstream early childhood educators—an under-researched group that plays a pivotal role in children's language and identity development—in the rapidly diversifying country, South Korea. Our qualitative analysis of interviews with nine teachers revealed a tendency toward monolingual, Korean-centered ideology and deficit-oriented views that pathologized multilingualism with some exceptions where few teachers showed openness to languages other than Korean. These findings have implications for teacher training programs and highlight some of the challenges to realizing genuinely inclusive education for CLD children in South Korea.